Democracy and Development: The Devil in the Details - Persson, Torsten; Tabellini, Guido (American Economic Review, 2006)
Does democracy promote economic development? This paper reviews recent attempts to address this question that exploited within-country variation. It shows that the answer is largely positive, but also depends on the details of democratic reforms. First, the sequence of economic vs political reforms matters: countries liberalizing their economy before extending political rights do better. Second, different forms of democratic government lead to different economic policies, and this might explain why presidential democracy leads to faster growth than parliamentary democracy. Third, it is important to distinguish between expected and actual political reforms. Taking expectations of regime change into account helps identify a stronger growth effect of democracy.